The RANCANG BANGUN ALAT KEJUT LISTRIK UNTUK PERIKANAN TUNA HANDLINE SKALA KECIL - Shidiq Lanang Prasetiyo; Sugeng Hari Wisudo; Roza Yusfiandayani (Fakultas Perikanan dan Ilmu Kelautan, 2021)
Tuna handline in Indonesia is a small-scale fishery and is generally not equipped with a fishing rod. This often causes fishermen to face various problems such as excessive workloads and a decrease in the quality of the catch when the fishing line is eaten by relatively large tuna (>10 kg). This is research has a final goal, namely to make an electric shock device that is ready to be used by tuna fishing line fishermen. This is a preliminary research aiming to determining a list of component requirements and making a design for an electric shock device. The method used is literature study and experiment. The results of the research on determining the list of component requirements showed that the type of DC electric shock was used as an electric shock for fish. Meanwhile, the switch system uses a timer delay relay. Furthermore, based on the results of the calculation of material selection, it shows that stainless steel is the first priority with a C value of 1. The tube shape is chosen as the main shape design because it has the fastest speed and travel time compared to other forms, namely 2.84 m/sec and 35.27 seconds. The construction for assembling a single electric shock device requires at least 26 components. The results of the research on making prototypes that have been made have dimensions of 6 cm in diameter and a total height of 40 cm and a prototype weight of 2.67 kg.